Flexible and porous catalyst electrodes constructed by Co nanoparticles@nitrogen-doped graphene films for highly efficient hydrogen evolution1. Issue 31 (21st August 2015) - Hou, Dongman; Zhou, Weijia; Zhou, Kai; Zhou, Yucheng; Zhong, Jing; Yang, Linjing; Lu, Jia; Li, Guoqiang; Chen, Shaowei
<x xml:space="preserve">Abstract</x> A flexible and porous electrode composed of cobalt nanoparticles embedded into a N-doped graphene film exhibits remarkable HER catalytic activity.